The relationship between gut microbiota and susceptibility to type 2 diabetes mellitus in rats - Yongcheng An; Hongyu Dai; Yuhui Duan; Long Cheng; Lu Shi; Changhao He; Chen Wang; Yinglan Lv; Huimin Li; Huilin Zhang; Yan Huang; Wanxin Fu; et al. (BMC, 2023)
Abstract Purpose The purpose of this study is to investigate the relationship between the susceptibility to type 2 diabetes and gut microbiota in rats and to explore the potential mechanism involved. Methods Thirty-two SPF-grade SD rats were raised as donor rats, and divided into control, type 2 diabetes mellitus (T2DM, fasting blood glucose ≥ 11.1 mmol/L), and Non-T2DM (fasting blood glucose < 11.1 mmol/L) groups. Feces were collected and prepared as fecal bacteria supernatants Diab (fecal bacteria supernatant of T2DM group rats), Non (fecal bacteria supernatant of Non-T2DM group rats), and Con (fecal bacteria supernatant of control group rats). Another seventy-nine SPF-grade SD rats were separated into normal saline (NS) and antibiotics (ABX) groups and given normal saline and antibiotics solutions, respectively. In addition, the ABX group rats were randomly separated into ABX-ord (fed with a 4-week ordinary diet), ABX-fat (fed with a 4-week high-fat diet and STZ ip), FMT-Diab (with transplanted fecal bacteria supernatant Diab and fed with a 4-week high-fat diet and STZ ip), FMT-Non (with transplanted fecal bacteria supernatant Non and fed with a 4-week high-fat diet and STZ ip), and FMT-Con (with transplanted fecal bacteria supernatant Con and fed with a 4-week high-fat diet and STZ ip) groups. Furthermore, the NS group was randomly divided into NS-ord (fed with a 4-week ordinary diet) and NS-fat (fed with a 4-week high-fat diet and STZ ip) groups. After this, the short-chain fatty acids (SCFAs) in the feces were detected using gas chromatography, and the gut microbiota were detected using 16S rRNA gene sequencing. Finally, G protein-coupled receptor 41 (GPR41) and GPR43 were detected by western blot and quantitative real-time polymerase chain reaction. Results G__Ruminococcus_gnavus_group were more abundant in the FMT-Diab group compared to the ABX-fat and FMT-Non groups. The levels of blood glucose, serum insulin, total cholesterol, triglycerides, and low-density lipoprotein cholesterol were also higher in the FMT-Diab group compared to those of the ABX-fat group. Compared to the ABX-fat group, both the FMT-Diab and FMT-Non groups had higher contents of acetic and butyric acid, and the expression of GPR41/43 were significantly higher as well. Conclusions G__Ruminococcus_gnavus_group might make rats more susceptible to T2DM; T2DM-susceptible flora transplantation increased the susceptibility to T2DM in rats. Additionally, gut microbiota-SCFAs-GPR41/43 may play a role in the development of T2DM. Lowering blood glucose by regulating gut microbiota may therefore become a new strategy for the treatment of T2DM in humans.